Nuevo enfoque del negocio de las tarjetas bancarias en Espa\~na y el nuevo papel a desarrollar por el comerciante - Carlos Castillo Peces; Carmelo Mercado Idoeta; Daniel Corral de la Mata (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
The objective of this research is to analyze the basics elements of the Spanish financial entities new approach in the financial cards business, as well as the merchant's new role in its development. For this purpose, a questionnaire was sent to 60 managers in the cards business in such entities. After analyzing the results of the 44 received questionnaires, we may conclude that this new approach should focus in promoting revolving and installment operations through financial cards. Additionally, it is verified that the merchants will need to play a relevant and rewarded role in promoting and prescribing these finance operations
Keywords: G21; 330; financial cards; interchange rates; financial institutions management